TECHNIQUES FOR THE ISOLATION AND PURIFICATION OF SARCOCYSTIS AUCHENIAE OOCYSTS FROM SMALL INTESTINE OF EXPERIMENTALLY INFECTED DOGS - Zacarías S., Fiorella (2013)
Procedures were evaluated for the rapid and efficient purification of oocysts and esporocysts of Sarcocystis aucheniae (Sa) from the small intestine of experimentally infected dogs with 400 Sa macrocysts obtained from meat of naturally infected alpacas. The mucosa of the small intestine was removed. Samples were washed by centrifugation with PBS, homogenized and centrifuged. Large quantities of oocysts attached to the intestinal microvilli were obtained. In the first procedure, an ezimatic treatment with 5% tripsin was used resulting in 50% oocyst separation. In the second procedure samples were treated with 2.6% sodium hypoclorite solution achieving 80% separation. In the third procedure, samples were centrifuged with a discontinuous density gradient of potassium bromide rendering 99% oocyst separation. The later procedure allowed obtaining relevant quantities of purified Sa oocysts and without loss of viability.